Dental caries among Finnish teenagers participating in physical activity and diet intervention: association with anthropometrics and behavioural factors - Mirja Methuen; Sofia Kauppinen; Anna Liisa Suominen; Aino-Maija Eloranta; Juuso Väistö; Timo Lakka; Hannu Vähänikkilä; Vuokko Anttonen (BMC, 2021)
Abstract Background An association between childhood anthropometric measurements and dental caries is conflicting. The prevalence and severity of dental caries and its association with anthropometric and behavioural factors, were investigated among Finnish teenagers. Methods The study sample comprised 202 15-17-year-old participants in the Physical Activity and Nutrition in Children (PANIC) Study. Dental caries findings were recorded using International Caries Detection and Assessment System (ICDAS) criteria, including activity estimation; numbers of decayed teeth (DT) and decayed, missing and filled teeth (DMFT) were recorded. Body weight, height and waist circumference were measured and respective body mass index (BMI) was calculated. Body fat percentage was assessed by dual-energy X-ray absorptiometry. Health-related behaviours and consumption of food and drinks were assessed using questionnaires, and intake of nutrients using a 4-day food record. Results Mean DMFT for all the participants was 2.4 (SD = 2.9), DT 0.6 (SD = 1.3), and 36% had DMFT = 0. No difference between genders was observed. In bivariate analyses, use of sugar-sweetened beverages (SSB) three times or less per week and not having used snuff associated significantly, whereas higher carbohydrate intake (E%), toothbrushing less often than twice a day and higher caries experience at baseline almost significantly with DT > 0. In adjusted regression analyses, frequent use of SSB and higher carbohydrate intake increased the odds for DT > 0. Additionally, higher carbohydrate intake (E%) and infrequent tooth brushing significantly associated with a higher number of DT. Conclusion Caries prevalence is still low and similar in Finnish teenage girls and boys. Behavioural factors are, but anthropometric factors are not associated with dental caries.